Campus 5.0: Monitoring Vehicle Emissions for More Sustainable Mobility - Janaina Antonino Pinto; Ester Divieso Roman Rodrigues; Orlando Fontes Lima Junior; Juliana Freitag Borin; Tania Almeida; Leandro Tiago Manera; Ieda Kanashiro Makiya; Henrique Candido de Oliveira; Rafael Pereira de Sousa; Rachel de Carvalho Paschoalino; Vanderlei Braga; Thalita dos Santos Dalbelo (Universitas Diponegoro, 2024)
The university campuses are like microcities, providing employees and students with social opportunities and essential services in addition to their core educational activities (teaching, research, and outreach). The smart campus is a growing trend that makes efficient use of infrastructure by integrating smart technologies for decision-making and advancing sustainability goals. The mobility and transport project at the Unicamp University campus is part of the Smart Campus Management Technical Chamber, and the Campus 5.0 concept is aligned with several sustainable development goals outlined in the UN's 2030 Agenda. This proposal aims to develop an inventory of vehicle emissions, establish the connectivity of the information and communication network to analyze the impacts of vehicles on local air quality, and structure support models for decision-making, in addition to presenting practical solutions implemented at Unicamp aiming at greater sustainability of the campus. The information and communication network will allow the collection and analysis of data in real time, providing accurate and updated information on vehicle emissions and air quality in the campus area. Decision support models will be developed, which will allow the definition of policies and actions to promote sustainable mobility on campus, contributing to the creation of a healthier and more sustainable university environment. These results will aid university administrators in improving Green Metrics' key performance indicators.